Potret Prosesi Tradisi Rasulan Di Kabupaten Gunungkidul - Heri Kuswanto; Ricy Fatkhurrokhman; Khoirul Anam; Ahmad Syafii Rahman (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2021)
The Rasulan tradition is synonymous with the coastal communities of Gunungkidul. This tradition is used as a means of worship and offerings to spirits, the spirits of the ancestors of the gods and the rulers of the universe. Considering that this tradition is related to the belief system, the people on the coast of Gunungkidul still believe in and carry out this tradition with full awareness, comfort and holiness. Until now, the authenticity of the apostolic tradition has been preserved, starting from the time and place of implementation, the uborampe, the rites and the arts. Even though they have adapted to Islam and contemporary culture, the majority of people on the coast of Gunungkidul still have mystical beliefs about the various rites and offerings that are in the apostolic procession. After researching using qualitative data-based field research then analyzed by descriptive analysis method using various theories, it can be concluded that the people on the coast of Gunungkidul still believe in the mystical values ​​that exist in the rites and uborampe of the apostolic tradition. These values, among others, are the value of worship of spirits and ancestral spirits, the value of asking for safety, rejecting danger, freedom from prayer, togetherness, religion, mutual assistance, mutual assistance and the value of giving thanks to God.